Comparative Analysis of Windings and Vector Groups in 20/0.4 kV Distribution Transformers at CV. Centrado Prima - Hidayat, Taopik; Dionova, Brainvendra Widi; Wilyanti, Sinka; Mohammed, M. N. (Eksergi, 2022)
Turn ratio test is a comparison test of the number of secondary turns with the primary turns on the transformer. The turns ratio and group vector testing is one of the routine transformer tests. This test generally uses the Transformer Turns Ratio (TTR) test tool, the test equipment used sometimes experiences technical and non-technical problems so a comparative test method is needed to get a good analysis. The research method used is observational research and literature study, namely analyzing the transformer to be studied by conducting TTR testing in two ways, namely testing with test equipment and three-phase low voltage sources, aiming to obtain a very good level of accuracy. The test results were analyzed and compared with theory and calculations, with reference to the IEC 60076-1 standard. The results of the comparison of windings and group vectors using TTR 100 test equipment and a 3-phase low voltage source (TVR) show the same conclusions as the results of the analysis, where the first transformer sample is in normal condition and meets the requirements. SPLN D3.002-1:2007 or IEC Standard 60076-1. While the second sample transformer is in an abnormal condition in the W winding where the difference value is above 0.5%.